STRATEGI PENGEMBANGAN SISTEM JARINGAN TRANSPORTASI DI KOTA MANADO - Ivon M. Mangundap; Charles N. Ngangi; Caroline B. D. Pakasi (Sam Ratulangi University, 2017)
This research was conducted in Manado City, North Sulawesi Province. Data to be used in this research is primary data and secondary data. Primary data were obtained from direct interviews with land transportation users. Secondary data were obtained from various publications issued by the Central Bureau of Statistics Manado City and Regional Agencies related to this research. This research uses SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats), with analysis of development of transportation sub sector using External Internal matrix. The results of this study indicate that the strategy that can be set for the development of transportation network system in Manado City are Development of existing transportation network in Manado City, based on geographical potential and natural resources owned by looking at opportunities from the tourism and transportation sectors potential for the development of sea and coastal transportation, increased discipline of riders, passengers and pedestrians, balancing the percentage of vehicles and minimizing, congestion level with good parking location arrangement, maximize the development of road network in Manado City by optimizing the distribution of goods and human to the transportation of the feeder (transportation between environments) and maximize the integration of modes to access new road network, Improve the quality of human resources for the users Public transport needs to be done so that they are really ready to carry out transportation services to the general public as well as improve the discipline of utilization of driving license to minimize the users of motor vehicles.